2022
DOI: 10.1200/jco.21.02488
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Risk Stratification of Early-Stage Melanoma Micrometastases From an International Multicenter Study: Implications for the Management of American Joint Committee on Cancer IIIA Disease

Abstract: PURPOSE Indications for offering adjuvant systemic therapy for patients with early-stage melanomas with low disease burden sentinel node (SN) micrometastases, namely, American Joint Committee on Cancer (AJCC; eighth edition) stage IIIA disease, are presently controversial. The current study sought to identify high-risk SN-positive AJCC stage IIIA patients who are more likely to derive benefit from adjuvant systemic therapy. METHODS Patients were recruited from an intercontinental (Australia/Europe/North Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…group is no different from that of the SNBgroup. 4,26 Our data would indicate that the additional information afforded by the SNB for pT4b melanomas is limited, with no low-risk nodal micrometastatic disease in the SNB? group and no difference in DSS between the SNB-and SNB?…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…group is no different from that of the SNBgroup. 4,26 Our data would indicate that the additional information afforded by the SNB for pT4b melanomas is limited, with no low-risk nodal micrometastatic disease in the SNB? group and no difference in DSS between the SNB-and SNB?…”
Section: Discussionmentioning
confidence: 92%
“…1 Recently, a multinational consortium identified a subgroup of putatively low-risk AJCC IIIA patients with a greatly increased risk of recurrence and/or death, based on disease burden in the SN, measured as the maximum tumor deposit size (MTDS). 4 At the other end of this spectrum, the indications for offering adjuvant systemic therapy to patients with intermediate-to high-risk AJCC stage III, namely IIIB-IIID, melanoma have largely been standardized internationally. 5,6 Accordingly, all patients with pT2b-pT4b melanomas and a positive SNB are now considered for adjuvant systemic therapy without consideration of the burden of disease in the metastatic nodes, which could potentially have a bearing on conversations with patients regarding the benefits from treatment and the risks from toxicity and overtreatment.…”
mentioning
confidence: 99%
“…This work by Hussain et al 3 is an extension of the research recently undertaken by an international consortium, which stratified the risk recurrence and death in a pT1b-pT2a SNB-positive (American Joint Committee on Cancer [AJCC] IIIA) cohort of patients. 4 In that study, maximum tumor deposit size (MTDS) was found to be the optimal phenotypical biomarker for this ostensibly low-risk group. The latest analysis of the current authors found that MTDS also was an important stratifying phenotypical biomarker for SNB-positive pT2b-pT4a primary melanomas, and that value was constant at 0.7 mm.…”
Section: Presentmentioning
confidence: 96%
“…The article from Moncrieff et al 1 addresses the critical question of selecting patients with a higher risk of relapse among those diagnosed with stage IIIA melanoma who present with a micrometastasis in the lymph nodes (tumor deposit in lymph nodes measuring < 1 mm). From a surgical perspective, the MSLT-II study established the current standard of care for patients with stage III melanoma in favor of sentinel lymph node dissection, followed by sonographic observation for 5 years.…”
Section: To the Editormentioning
confidence: 99%